Al ‘Anãṣiru al Jauhãriyyatu fī Filmi al Rasūmi al Mutaharrikati ‘Ãliyan (UP)" Lipete Duktir (Dirãsatun Taḥlīliyyatun fī ‘Ilmi al Adabi) - Gumilang, Muhammad Fajar; Daud, Izzat Muhammad; Muttaki, Muttaki (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
Film Up is an American CGI animated comedy-drama adventure film with an adventure genre, which tells of an old man who travels to paradise fall, this film was produced by Pixar Animation Studios and released by Walt Disney Pictures in 20090. Researchers discuss the intrinsic elements in the film UP by Pete Docter in 2009. This study uses descriptive qualitative research with data collection methods through written documents that can support this research, especially the intrinsic elements of the film. The aims of this study were 1) to find out the intrinsic elements in the film Up by Pete Doctor 2) to find out the lessons contained in the film Up Pete Doctor. The theory used in this study is the literary theory of intrinsic elements. The results of this study show: 1) The intrinsic elements in Pete Dokter's film Up are: Film title: UP, Type of Film, Animation, Adventure, Comedy Director: Pete Doctor, Bob Peterson Production: Pixar Animation Studios, Plot: Advanced, Message: If If you want to come true, you really are in pursuit of it. Characters: Carl Fredickson, Elie, Rusl, Chales Muntz, Dug, Alpha. 2) The wisdom in the film up by pete docter is: Having dreams to achieve, Not giving up easily, Courageous, Please help, Caring, The five wisdoms that researchers found in the film Up can be used as a reference for us in behaving, because everything that is obtained is impressive positive for the audience